(3GdeONd Gdi af GdeaGhVGJ (B/s - (3Ydj, eMehOs; (3GdgRGjeI, eMeO YhV s ((3YeGf(B: s (3OGQ GdMGeO ddfTQ h GdJhRjY(B, s, 2006)
(3eONd Gdi af GdeaGhVGJ GVGaI Gdi VhGHW GdYedjGJ GdJaGhVjI h GdUQGY h GdMdhd h cPG eQGMd GdYedjI GdJaGhVjI h aj GdGNjQ JfGhd GdYhGed GdeDKQI aj GdYedjGJ GdJaGhVjI(B.s
(3eQGLY U(B.158s
Keywords: (3GdeaGhVGJs